Handbook of developmental psychology (Prentice-Hall, 1982)
The Handbook of Developmental Psychology is a comprehensive, authoritative yet frontier-pushing overview of the study of human development presented in a single-volume format. It is ideal for experienced individuals wishing for an up-to-date survey of the central themes prevalent to developmental psychology, both past and present, and for those seeking a reference work to help appreciate the subject for the first time.